On the freezing method for nonlinear nonautonomous systems with delay. (2001) - Gil', Michael I.
Abstract : Nonlinear nonautonomous differential systems with delaying argument are considered. Explicit conditions for absolute stability are derived. The proposed approach is based on the generalization of the freezing method for ordinary differential equations.